Placing the photographic image in contemporary Spanish photocine (Significação: Journal of Audiovisual Culture, 2013)
The article analyzes three recent films produced in Spain which the photographic gains movement in the picture to consider today like a new category, as photocine. The films analyzed are: Unas fotos en la ciudad de Sylvia (Luis Guerin, 2007, 67’); El Pabellón Alemán (Juan Millares, 2009, 14’); and El Baobab de piedra (Marco Potyomkin, 2010, 86’).